EFFECTS OF SEPARATE AND COMBINED USAGE OF DERIVATIVE OF PEPTIDEAMINOBENZOPHENONES AND OF DIAZEPAM ON RAT’S BEHAVIOR IN “OPEN FIELD” TEST - Pogorelaya, I.V. (World of Medicine and Biology, 2010)
The comparative investigation of peculiarities of investigative behavior of Wistar rats in «open field» revealed dosage-depended character of it’s suppression both under condition of diazepam (0,05-0,75 mg/kg, i.p.) and derivative of peptideamidobenzophenones (PABPh) (0,015-1,5 mg/kg, i.p.) administration. ED50 of diazepam which effectively blocked rearings without support in one half of animals was 0,87 mg/kg and 0,14 mg/kg for derivative of PABF. ED50 of diazpeam which effectively suppress the rat’s ability to cross central squares was 0,43 mg/kg and 1,43 mg/kg for derivative of PABF.